Motor Proficiency and Generalized Self-Efficacy Toward Physical Activity in Children With Intestinal Failure. Issue 1 (January 2019) - So, Stephanie; Patterson, Catherine; Evans, Cathy; Wales, Paul W.
ABSTRACT: Objective: Survival rates of children with intestinal failure have increased; however, associated co-morbidities may affect long-term motor developmental outcomes. This study evaluates motor proficiency and generalized self-efficacy toward physical activity (PA) in children ages 6 to 12 years with intestinal failure. Methods: This is an observational, cross-sectional study of children followed in a multidisciplinary intestinal rehabilitation program. Motor proficiency was assessed using the Bruininks-Oseretsky Test of Motor Proficiency-2 Short Form (BOT-2 SF) and the Scales of Independent Behavior (parent-proxy report). Children completed the Children's Self-Perceptions of Adequacy in and Predilection for Physical Activity (CSAPPA) and a PA questionnaire. Relevant demographic and medical variables were correlated with assessment results. Results: Participants include 30 children (18 males), median age 7 years (interquartile range [IQR] 6–9) with gestational age 35 weeks (IQR 32–39) and birth weight 2.13 kg (IQR 1.68–2.77). Thirteen (43%) were dependent on parenteral nutrition. Fifteen (50%) scored below average on the BOT-2 SF. Lower BOT-2 SF scores were significantly associated with lower CSAPPA scores ( r = 0.480, P = 0.01), with a common barrier to PA being the presence of a central line or enterostomy tube. Gestational age, height z scores, length of hospital admissions, and number of septic events were all significantly correlated with lower scores in motor proficiency. Number of septic events and total parenteral nutrition days were significant predictors of lower BOT-2 SF scores, when adjusting for birth weight. Conclusions: Multiple medical variables related to intestinal failure may affect motor proficiency and PA self-efficacy. Developmental follow-up is important to optimize motor skill development and promote PA participation.